Synthesis, biological evaluation, and physicochemical property assessment of 4-substituted 2-phenylaminoquinazolines as Mer tyrosine kinase inhibitors. Issue 13 (1st July 2016) - Wang, Sheng-Biao; Cui, Mu-Tian; Wang, Xiao-Feng; Ohkoshi, Emika; Goto, Masuo; Yang, De-Xuan; Li, Linna; Yuan, Shoujun; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung; Xie, Lan
Graphical abstract: Abstract: Current results identified 4-substituted 2-phenylaminoquinazoline compounds as novel Mer tyrosine kinase (Mer TK) inhibitors with a new scaffold. Twenty-one 2, 4-disubstituted quinazolines (series4 –7 ) were designed, synthesized, and evaluated against Mer TK and a panel of human tumor cell lines aimed at exploring new Mer TK inhibitors as novel potential antitumor agents. A new lead, 4b, was discovered with a good balance between high potency (IC50 0.68 μM) in the Mer TK assay and antiproliferative activity against MV4-11 (GI50 8.54 μM), as well as other human tumor cell lines (GI50 < 20 μM), and a desirable druglike property profile with low log P value (2.54) and high aqueous solubility (95.6 μg/mL). Molecular modeling elucidated an expected binding mode of4b with Mer TK and necessary interactions between them, thus supporting the hypothesis that Mer TK might be a biologic target of this kind of new active compound.